Ameliorative effects of Schisandrin B on Schistosoma mansoni-induced hepatic fibrosis in vivo. - Ho Yin Pekkle Lam; Ting-Ruei Liang; Shih-Yi Peng (Public Library of Science (PLoS), 2021)
Schistosomiasis is second only to malaria as the most devastating parasitic disease in the world. It is caused by the helminths Schistosoma mansoni (S. mansoni), S. haematobium, or S. japonicum. Typically, patients with schistosomiasis suffer from symptoms of liver fibrosis and hepatosplenomegaly. Currently, patients were treated with praziquantel. Although praziquantel effectively kills the worm, it cannot prevent re-infection or resolve liver fibrosis. Also, current treatment options are not ample to completely cure liver fibrosis and splenic damages. Moreover, resistance of praziquantel has been reported in vivo and in vitro studies. Therefore, finding new effective treatment agents is urgently needed. Schisandrin B (Sch B) of Schisandra chinensis has been shown to protect against different liver injuries including fatty liver disease, hepatotoxicity, fibrosis, and hepatoma. We herein investigate the potential of using Sch B to treat S. mansoni-induced liver fibrosis. Results from the present study demonstrate that Sch B is beneficial in treating S. mansoni-induced liver fibrosis and splenic damages, through inhibition of inflammasome activation and apoptosis; and aside from that regulates host immune responses. Besides, Sch B treatment damages male adult worm in the mice, consequently helps to reduce egg production and lessen the parasite burden.